A Report of Two Patients with Darier Disease and Hidradenitis Suppurativa. Issue 4 (10th June 2016) - Ornelas, Jennifer; Sivamani, Raja; Awasthi, Smita
Abstract: We report two unique cases of patients with Darier disease and hidradenitis suppurativa. Although it is unknown whether there is a connection between the two diseases, it is possible that an interaction between sarcoendoplasmic reticulum calcium transport ATPase and Notch homolog 1, translocation‐associated (Drosophila) caused both diseases in these individuals.